Archaeology of early colonial interaction at El Chorro de Maíta, Cuba - Valcárcel Rojas, Roberto (Ripley P. Bullen series, 2016)
Roberto Valcárcel Rojas analyses the construction of colonial authority and the various attitudes and responses of natives and other ethnic groups. His pioneering study reveals the process of transculturation in which new individuals emerged and helps construct the vital link between the pre-Columbian world and the development of an integrated and new history.